Testing Various Types of (CSOL) Speakers - Jelaska, Zrinka (Array, 2008)
Assessment of language proficiency for the CSOL learner (Croatian for speakers of other languages) shares some of the features with assessment of other languages, but also has some specifities, those shared by other less widely thought languages, those shared by other structurally similar languages (esp. morphologically) or those that are more specific. Temporary and permanent migrants to Croatia need to take Croatian language tests for variety of purposes, as in other countries. But speakers of CSOL which should take tests may be very different, which causes some serious problems for testers (some similar to the problems in ESOL and other languages, some not). This paper is a theoretical study which will concentrate on that aspect of (Croatian) language assessment: testing various types of CSOL learners/speakers. It will be grounded on some SLA research findings, but deal with topics which need more investigation as there is no consensus among various theoretical and empirical studies or researchers. Those are: age as a critical factor for testing (esp. testing of very old speakers), L1 influence (esp. testing speakers of closely related languages and heritage speakers), testable competences (esp. testing illiterate people, or those with special needs such as SLI, dyslexia etc.). Its objective is to raise awareness of the problem of testing people regardless of their age, education level, literacy skills and L1.